Inflammasome activation in preeclampsia and intrauterine growth restriction. (17th August 2022) - Silber, Michal; Dekel, Nadav; Heusler, Ishai; Biron‐Shental, Tal; Amiel, Aliza; Kidron, Debora; Weisz, Avivit; Benchetrit, Sydney; Zitman‐Gal, Tali
Abstract: Problem: Preeclampsia (PE) and intrauterine growth restriction (IUGR) are leading causes of perinatal complications, affecting 8%–10% of all pregnancies. Inflammasomes are suspected to be one of the mechanisms that lead to the process of term and preterm labors. This study evaluated the inflammasome‐dependent inflammation processes in placental tissue of women with PE and IUGR. Methods of Study: In this prospective cohort study, 14 women with PE, 15 with placental‐related IUGR and 19 with normal pregnancy (NP) were recruited during admission for delivery. Maternal blood was obtained prior to delivery and neonatal cord blood and placental tissue were obtained after delivery. Results: NLRP7 and PYCARD protein expression were higher in placental PE and IUGR samples versus NP samples. Immunostaining revealed that NLRP7 and PYCARD were upregulated in PE and IUGR placental syncytiotrophoblast, stroma and endothelial cells. PYCARD serum levels were significantly higher in women with PE and IUGR. No significant changes were observed in neonatal cord blood. Conclusions: NLRP7 and PYCARD are key inflammatory proteins that are significantly elevated in PE and IUGR. Better understanding their significance may enable them to become markers of prediction or progression of PE and IUGR.